The Effect of Interactive Mutimedia Based on Articulate Storyline 3 on Student Learning Outcomes in Elementary Schools - Mesyaluna Dinda Anadira; Rizka Novi Irmaningrum; A.F. Suryaning Ati MZ (Universitas Negeri Medan, 2025)
This study aims to determine the effect of interactive multimedia base on articulate storyline 3 on student learning outcomes in elementary schools. This study uses quantitative research with a quasi-experimental method of the non-equivalent control group type. The samples used were class IV A and class IV B, each consisting of 15 students. Data coloction techniques ised were validation, observation and cognitive earning outcome tests. While the collected data were analyzed in two ways, namely prerequisite test were used to ensure the feasibility of the data including normality tests and homogeneity test. Hypothesis testing was used to determine the effect of independent variables on dependent variables using independent sample t-tests. Thus, the results show that the average value of the experimental class is higher than the control class in all three domains of learning outcomes. The t-test produces a Sig. (2-tailed) value of 0.000 (<0.05), which indicates a significant change in the use of interactive multimedia based on articulate storyline 3 on student learning outcomes.